A 56-nm CMOS 99-mm2 8-Gb Multi-Level NAND Flash Memory With 10-MB - Takeuchi, K.
A single 3.3-V only, 8-Gb NAND flash memory with the smallest chip to date, 98.8 mm2, has been successfully developed. This is the world's first integrated semiconductor chip fabricated with 56-nm CMOS technologies. The effective cell size including the select transistors is 0.0075 mum2 per bit, which is the smallest ever reported. To decrease the chip size, a very efficient floor plan with one-sided row decoder, one-sided page buffer, and one-sided pad is introduced. As a result, an excellent 70% cell area efficiency is realized. The program throughput is drastically improved to twice as large as previously reported and comparable to binary memories. The best ever 10-MB/s programming is realized by increasing the page size from 4kB to 8kB. In addition, noise cancellation circuits and the dual VDD-line scheme realize both a small die size and a fast programming. An external page copy achieves a fast 93-ms block copy, efficiently using a 1-MB block size
Keywords: 10 Mbits/s.; 3.3 V; 4 kbit; 56 nm; 8 Gbit; 8 kbit; 93 ms; CMOS technologies; NAND flash memory; Binary memories; High-speed programming; Integrated semiconductor chip; Multilevel cell; Noise cancellation circuits